A compactness result for non-local unregularized gradient flow lines - Albers, Peter; Frauenfelder, Urs; Schlenk, Felix (Journal of fixed point theory and applications, 2019)
We prove an abstract compactness result for gradient flow lines of a non-local unregularized gradient flow equation on a scale Hilbert space. This is the first step towards Floer theory on scale Hilbert spaces.
Gesehen am 27.03.2019